2015
DOI: 10.1111/apa.12921
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for poor neonatal adaptation after exposure to antidepressants in utero

Abstract: Formula feeding and exposure to SSRIs were associated with development of PNA, but dosage was not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…This suggestion might have resulted in the transient and self-limiting neonatal adjustment syndrome. A study that supports our results revealed that newborns who were exposed to antidepressants in the prenatal period and were breastfed were less likely to develop poor neonatal adaptation syndrome than those who were fed by formula [33]. A metaanalysis revealed a lower ratio of breastfeeding in women who had antenatal depression than in nondepressed women [16].…”
Section: Discussionsupporting
confidence: 86%
“…This suggestion might have resulted in the transient and self-limiting neonatal adjustment syndrome. A study that supports our results revealed that newborns who were exposed to antidepressants in the prenatal period and were breastfed were less likely to develop poor neonatal adaptation syndrome than those who were fed by formula [33]. A metaanalysis revealed a lower ratio of breastfeeding in women who had antenatal depression than in nondepressed women [16].…”
Section: Discussionsupporting
confidence: 86%
“…In mother-infant dyads whereof the infants were formula-fed, the intervention rate was higher. An earlier study of our research group showed that formula-fed infants develop more symptoms of poor neonatal adaptation, which could explain this finding [24]. However, other factors, such as the type of psychotropic drugs (some are not compatible with breastfeeding) and severity of psychiatric disorder might also attribute to this relationship.…”
Section: Discussionmentioning
confidence: 81%
“…The type of underlying psychiatric disorder and severity of psychiatric symptoms might attribute to this relationship. PNA does not seem to be related to the antidepressant dosage [13, 24]. In mother-infant dyads whereof the infants were formula-fed, the intervention rate was higher.…”
Section: Discussionmentioning
confidence: 99%
“…There is also some evidence to suggest breastfeeding reduces the risk of developing symptoms. 14 More recent studies have suggested potential neurodevelopmental consequences beyond the first few days of life with research demonstrating lower motor scores and increased stress signs throughout the first month of life in babies of mothers treated with SSRIs compared with those with untreated depression. 15 Additionally, there is evidence of subtle electroencephalogram changes in neonates exposed to SSRIs in utero compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%